Peroxisome Proliferator Activated Receptor-Gamma Ligands as Potent Antineoplastic Agents - Theocharis, S.; Margeli, A.; Kouraklis, G. (Current Medicinal Chemistry - Anti-Cancer Agents, 2003)
The Peroxisome Proliferator Activated Receptors (PPARs) are initially described as molecular targets for compounds inducing peroxisome proliferation. Among the three PPAR subtypes (alpha, beta, gamma), PPAR-gamma acting as a ligand-activated transcription factor, proved to be an important regulator of adipogenic differentiation and glucose homeostasis. Recent data support evidence for participation of PPAR-gamma, upon ligands activation, in the biological mechanisms underlying the carcinogenic evolution. Specific PPAR-gamma ligands affect cancer cells proliferation and differentiation acting as cell cycle modulators, suggesting their use as an important tool for future therapeutic approach in cancer. In this review, the latest knowledge on PPAR-gamma activation and molecular mechanisms of PPAR-gamma ligands mediated anti-tumoral activity are presented. In vitro and in vivo studies concerning the use of PPAR-gamma ligands in different cancer types are also included.
Keywords: ppar-gamma